Rahi Shari'ati az kudam su (Khandaq sifr) . ; . "Shari'ati ansui-yi nifrinha va afarinha (Khandaq shumarahi-yi 32) (Irshad)
Shari'ati's path from which direction?; Shari'ati beyond praises and curses.